20 Factors influencing the discard of clinical tissue and NHSBT methods to maintain a low discard rate. (16th November 2022) - Usherwood, David; Roberts, Lauren; Woodward, Toni; Gallagher, Sam
Abstract : Introduction: NHS Blood and Transplant Tissue and Eye Services (TES) is a human multi-tissue, tissue bank supplying tissue for transplant to surgeons throughout the UK. NHSBT has two Eye Banks. These are NHSBT Filton, based in Bristol and NHSBT David Lucas Eye Bank, which is based in Speke Liverpool. Materials and Methods: NHSBT monitors our monthly discard rates with the aim to review for any patterns. Due to the NHSBT Eye Banks using a computer system called PULSE we can categorise all our discard for further analysis. Focusing on key areas such as Contamination, Corneal Assessment failure such as Low Endothelial Cell count, Medical deferrals and blood sample quality. Results: 2019- NHSBT Procured 5705 Eyes and Issued 4725. This is a discard rate of 19% 2020- NHSBT Procured 3725 Eyes and Issued 2676. This is a discard rate of 28% 2021- NHSBT Procured 4394 Eyes and Issued 3555. This is a discard rate of 19% Based on the EEBA Statistical report of Eye Banking Activity in Europe for 2019- 42663 Eyes/Corneas in situ were procured and 25254 Corneas supplied for transplant. This is a discard rate of 41%. Based on the EEBA Statistical report of Eye Banking Activity in for 2020- 33460 Eyes/Corneas in situ were procured and 21212 Corneas supplied for transplant. This is a discard rate of 37%. Discussion: Based on this data, NHSBT discard rate is below the European Average. Key factors which contribute to this low discard rate. Independent Clean rooms for excision and assessment operating to a Grade A Level. A centralised National Referral Centre and 4 dedicated Retrieval Teams ensure retrievals are within 24 hours of Death, and excision occur within 24 hours of enucleation. A dedicated Admin and Clinical Nursing Team performing the medical release ensures the Tissue is released promptly after Microbiological Testing (Day 10) for Assessment. During 2020 due to COVID all routine operations were cancelled suddenly. This resulted in an Increase of discard due to time expiry. References: EEBA Statistical report of Eye Banking Activity in Europe for 2019 and 2020.